EFEKTIVITAS PROGRAM KEGIATAN MAGANG BERSERTIFIKAT & STUDI INDEPENDEN (MSIB) DALAM UPAYA MENIINGKATKAN KERJA MAHASISWA/I UNIVERSITAS HKBP NOMMENSEN MEDAN - Saragih, Agnes Paskariani; Panjaitan, Maringan; Tobing, Artha L (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to evaluate the effectiveness of the Certified Internship and Independent Study (MSIB) Program in improving the work readiness of students at HKBP Nommensen University, Medan. The MSIB program is part of the Independent Campus policy launched by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) to bridge the gap between the world of education and the world of work. This program is designed to provide practical experience and skill development, both hard skills and soft skills needed in the world of work. This study uses a qualitative method with a descriptive approach. Data were collected through interviews with key informants (MSIB coordinators) and key informants (students who have participated in the MSIB program), as well as observation and documentation. Data analysis was carried out by identifying indicators of program effectiveness, namely program monitoring and socialization, target accuracy, achievement of objectives, and understanding of the program. The results of the study indicate that the MSIB program at HKBP Nommensen University Medan has been running well and effectively in improving students' work readiness. This program has succeeded in providing internship and independent study experiences that are relevant to industry needs, as well as developing skills such as communication, teamwork, adaptation, problem solving, and decision making. In addition, the MSIB program has also established close collaboration with various industry partners, which provides benefits for students and industry. Based on the research findings, it is concluded that the MSIB program needs to be continued and developed by the Ministry of Education, Culture, Research and Technology because it has proven effective in improving the quality of college graduates and preparing them to enter the workforce. This program also contributes to strengthening the link and match between the world of education and industry, as well as supporting the development of globally competitive human resources.